Alternative development : an anthology - Mendis, D. L. O.; Rotblat, Joseph, 1908-2005.; Sri Lanka Pugwash Group (Colombo : Sri Lanka Pugwash Group, 2005)
Includes papers presented at various Pugwash meetings.
v. 1. Pugwash. pt. 1, Remember your humanity, a tribute to Sir Joseph Rotblat. pt. 2, Remember your humanity, if you want peace, prepare for peace
Errata slip inserted in v. 1.
Includes bibliographical references.
Keywords: Rotblat, Joseph, -- 1908-2005.; Nuclear arms control; War -- Termination; Peace